Delayed and Chronic Sequelae of Trauma and the Role of the Interventional Radiologist - Wolf, Robert; Smolinski-Zhao, Sara (Seminars in Interventional Radiology, 2021)
In addition to acute injury requiring interventional radiologic treatments, patients with traumatic injuries can develop delayed or chronic complications. These injuries can involve nearly all solid organs in the abdomen. Coupled with significant improvements in visualizing these injuries with advanced imaging techniques such as minimally invasive procedures, nonoperative management of both acute traumatic injuries and their longer term sequelae has become the norm. This article reviews frequently seen complications of traumatic injury and their management by interventional radiologists.
Keywords: interventional radiology; trauma; complications; subacute injury; embolization; drainage